In search of success factors for a sustainable macro entrepreneurship and enterprise education policy: evidence from the European Union. (1st January 2015) - Mukhtar, Syeda–Masooda; Redman, James
The question addressed in this paper is whether macro policies can promote entrepreneurship and enterprise education through cultivating an 'Enabling Environment' that nurtures entrepreneurial culture and attitudes. Specifically, this question is investigated with respect to the formulation and implementation of 'Macro Entrepreneurship Policy' within the European Union (EU) which set out to deliver the European Council vision of declaring 'entrepreneurship as a key competence' for 'entrepreneurship education'. EU enterprise education initiatives are highlighted, and a UK 'good practice' example is presented as a case study. In view of the findings, the paper develops a 'Sustainable Macro Entrepreneurship Policy Model' with embedded Critical Success Factors that encapsulate the key elements of a policy framework needed for making better choices in formulating, developing, delivering and promoting entrepreneurship and enterprise education at a national level.